E-Commerce and Interest in Entrepreneurship (Case Study: Youth in Saba Village, Padang Panyabungan) - Rizka Ar Rahmah (Budapest International Research and Critics University, 2022)
This research, which was conducted in Saba Padang Village, Panyabungan Timur District, Mandailing Natal Regency, aims to analyze the influence of the presence of an e-commerce platform on Facebook social media on adolescent entrepreneurship interest in Saba Padang Village, East Panyabungan District. This study uses a descriptive qualitative approach, because this research is a social phenomenon that is shown by the subject to be studied. This research method was conducted by observing and interviewing 20 teenagers, the interview was conducted by asking 10 questions related to the research objectives. The results of this study were obtained, first, there was a desire from teenagers to carry out entrepreneurial activities, this was delayed due to the need for large capital. Second, The motivation of teenagers in Saba Padang Village is high, but they collide on several things such as capital and skills in marketing. Third, there is the influence of the existence of E-commerce with the interest of teenagers in carrying out entrepreneurial activities, because of the simple way of working with the existence of E-Commerce.